Dakwah Berbasis Moderasi Beragama : Studi Lembaga FKPMM Desa Linggoasri Kabupaten Pekalongan - Yudha Suripto Putra; Siti Ainun Musyarofah; Khoirul Muttaqin; Leli Maftuhah; Qomariyah (SETYAKI : Jurnal Studi Keagamaan Islam, 2025)
The FKPMM institution (Communication Forum for Mosque and Mushola Management) is one of the institutions that plays an important role in the development of Islamic da'wah with a religious moderation approach. In an increasingly complex global context, religious moderation is the key to maintaining social harmony and tolerance between religious communities. FKPMM, as an institution that focuses on developing da'wah through counseling and education, seeks to introduce balanced, tolerant and inclusive Islamic values. This research focuses on examining how FKPMM Institution builds religious moderation-based da'wah and creates inclusive and harmonious da'wah. In this case the theory used in religious moderation there are concepts, namely, tawasuth (middle attitude), tawazun (balance), and tasamuh (tolerance), which are the basis for religious moderation values. The research method used is using a qualitative approach based on field studies. There are research results that show how the FKPMM institution's da'wah strategy and the application of its inclusive da'wah, as well as a friendly and balanced da'wah approach that does not cause conflict in the community. Thus, FKPMM plays a strategic role as an agent of strengthening moderation values in society, and is relevant as a reference in the development of da'wah in other multicultural areas.